DAMPAK PENCEMARAN LINGKUNGAN LAUT SEBAGAI INSPIRASI DALAM PENCIPTAAN KARYA SENI LUKIS CAT AIR - Lutfiana Putri Munandar, Dafa; Akbar, Budiman (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
This research employs qualitative methods with an artistic research approach to create works that raise awareness of the importance of preserving the ocean from pollution. The artwork serves as a critique of the behavior of littering, visualizing the polluted sea using a realist style. Watercolor techniques such as wet on dry, wet on wet, and lifting off are applied on paper to produce works that reflect the actual conditions. The creation concept focuses on pragmatic, figurative art and modern aesthetics, with the aim of inspiring the protection of the marine environment in Indonesia.